Integration of the STEAM Approach in Learning Within the Merdeka Curriculum at the Elementary School Level: A Systematic Literature Review - Nabylla Sapta Ramadhani; Edo Wijaya (Universitas Negeri Surabaya, 2026)
This study aims to examine the integration of the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach in primary school learning and to analyze its alignment with the principles of the Merdeka Curriculum. This research employed a Systematic Literature Review (SLR) method guided by the PRISMA 2020 framework to ensure a transparent and structured selection process. The literature search was conducted across multiple academic databases, including Google Scholar, Garuda, and Web of Science, focusing on publications from 2021 to 2025. From an initial pool of 999 articles, 15 studies met the inclusion criteria and were analyzed using qualitative synthesis. The findings indicate that STEAM integration in primary education follows a systematic pattern grounded in constructivist and student-centered learning principles and is primarily implemented through Project-Based Learning (PjBL), Problem-Based Learning (PBL), and inquiry-based learning models. These approaches enable interdisciplinary and contextual learning experiences. Empirically, the implementation of STEAM has been shown to significantly enhance students’ 21st century competencies, including critical thinking, creativity, communication, and collaboration, as well as improving science literacy and problem-solving abilities. Furthermore, the STEAM approach demonstrates strong alignment with the Merdeka Curriculum by promoting independent learning, differentiated instruction, and the development of the Pancasila Student Profile. However, several challenges remain, particularly in terms of limited technological infrastructure, time constraints, and teachers’ pedagogical readiness in implementing integrative learning. Identified best practices include the use of STEAM-based digital modules, collaborative learning strategies, and continuous professional development for teachers. In conclusion, the integration of STEAM within the Merdeka Curriculum presents a promising framework for enhancing the quality of primary education, although its effectiveness depends on sustained institutional support, teacher capacity building, and adequate technological resources.